Compact Symmetric Objects. II. Confirmation of a Distinct Population of High-luminosity Jetted Active Galaxies - S. Kiehlmann; A. C. S. Readhead; S. O’Neill; P. N. Wilkinson; M. L. Lister; I. Liodakis; S. Bruzewski; V. Pavlidou; T. J. Pearson; E. Sheldahl; A. Siemiginowska; K. Tassis; et al. (The Astrophysical Journal, 2024)
Compact symmetric objects (CSOs) are compact (<1 kpc), jetted active galactic nuclei (AGN), whose jet axes are not aligned close to the line of sight, and whose observed emission is not predominantly relativistically boosted toward us. Two classes of CSOs have previously been identified: approximately one-fifth are edge dimmed and the rest are edge brightened. We designate these as CSO 1s and 2s, respectively. This paper focuses almost exclusively on CSO 2s. Using complete samples of CSO 2s we present three independent lines of evidence, based on their relative numbers, redshift distributions, and size distributions, which show conclusively that the vast majority (>99%) of CSO 2s do not evolve into larger-scale radio sources. These CSO 2s belong to a distinct population of jetted AGN, which should be characterized as “short-lived,” as opposed to “young,” compared to the classes of larger jetted AGN. We show that there is a sharp upper cutoff in the CSO 2 size distribution at ≈500 pc. The distinct differences between most CSO 2s and other jetted AGN provides a crucial new time domain window on the formation and evolution of relativistic jets in AGN and the supermassive black holes that drive them.